Tenacificação de polipropileno com elastômeros olefínicos para aplicações com requisitos de transparência ótica - Bulhões, Carolina Cerqueira Jordão Ribeiro (Universidade Federal de São Carlos, 2011)
The polypropylene is a versatile polymer but has lack of impact resistance. The polypropylene toughness is obtained thorugh the adition of elastomers that cause the loss of the blend stiffness. Many studies were performed in order to have the impact modification efficiency for different types of elastomers normally based on ethylene or styrene. The toughness mechanisms were also studied as well as the nucleant uses for minimizing the negative effect on blend stiffness reduction. The polypropylene blend morphology with containing elastomers, normally, presents two phases harming its transparency. Polypropylene is very used for applications where impact resistance is important but also the transparency like rigid packaging. Some studies were about polypropylene toughness in presence of clarifiers trying to get toughness with transparency. This work aims to evaluate the relation between toughness/ transparency of two types of random polypropylenes using different types of olefinics elastomers, ethylene based and propylene based with different density and molecular weight. The elastomers were added in different amounts, 10% and 20% wt. For the blends with PP12, EOC1 and EOC2 presented an excellent toughness/ stiffness balance. Regarding haze, these two elastomers reduced the blends transparency. PAO1 showed the best toughness/ transparency balance. For the blends with PP45, it was seen that EOC2 had the best toughness/ stiffness balance. However its transparency was reduced. PAO1 e PAO2 showed the best balance toughness/ transparency balance.
Polypropylene toughness with olefinics elastomers for applications with transparency needed
Keywords: Blendas poliméricas; Tenacificação; Transparência; Polipropileno; ENGENHARIAS